2013
DOI: 10.1016/j.gie.2012.07.031
|View full text |Cite
|
Sign up to set email alerts
|

Image-enhanced endoscopy for the diagnosis of colon neoplasms

Abstract: Autho

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
14
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(15 citation statements)
references
References 95 publications
(112 reference statements)
0
14
0
Order By: Relevance
“…A meta-analysis of several studies concerning the differentiation between colorectal adenomas and hyperplastic polyps showed that the accuracy of predictions of lesion pathology were 62% to 93% for NBI, 65% to 82% for while light endoscopy (WLE), and 69% to 96% for chromoendoscopy 10,15. The accuracy of pathological prediction by NBI was higher than that of WLE, and similar to that of chromoendoscopy.…”
Section: Narrow Band Imagingmentioning
confidence: 97%
“…A meta-analysis of several studies concerning the differentiation between colorectal adenomas and hyperplastic polyps showed that the accuracy of predictions of lesion pathology were 62% to 93% for NBI, 65% to 82% for while light endoscopy (WLE), and 69% to 96% for chromoendoscopy 10,15. The accuracy of pathological prediction by NBI was higher than that of WLE, and similar to that of chromoendoscopy.…”
Section: Narrow Band Imagingmentioning
confidence: 97%
“…Consequently, the user can distinguish between the two when undertaking the colonoscopy procedure (Cho, ). Studies have been conducted to compare AFI to white light colonoscopy, with one undertaken in 2013 which showed that AFI did not improve the detection rate (Fujiya & Kohgo, ); however, a study conducted three years earlier showed that AFI with a transparent hood increased the detection rates of polyps (Takeuchi et al, ). Another study conducted in 2013 compared the use of NBI, FICE, confocal laser endomicroscopy (CLE) and AFI to aid in the diagnosis of polyps in the colon (Wanders, East, Uitentuis, Leeflang, & Dekker, ).…”
Section: Commercial Colonoscopy Devices Performance and Market Analysismentioning
confidence: 99%
“…Novel methods were therefore developed to overpass anatomical difficulties of the colon, enable more accurate, even microscopic identification of abnormalities in the size, density and shape of crypts and vessels [13,[16][17][18]. They can be roughly divided into three categories, ones that improve overall mucosal examination and increase the polyp detection, those that enable more thorough examination (almost histological) of the detected lesions and minimally invasive techniques.…”
Section: Introductionmentioning
confidence: 99%